Análise da estrutura narrativa e regimes de interação em Assassin’s Creed Revelations - Barbosa, Jéssica de Amorim (2016)
This research aims to analyze the interaction schemes of the game Assassin's Creed Revelations through the intersection of social semiotics theoretical assumptions and the analysis model of the Greimasian generative route. Because it is a digital document, that shows a more dynamic content, immersive and that allows different forms of interaction, we decided to investigate how the production and meaning apprehension in a narrative that is built into acts, in this case, into the act of playing, happens. Based on the precepts of French semiotics, on the studies by authors such as Fiorin (2005), Bertrand (2003) and Landowski (2014), our research seeks to understand how a complex audiovisual narrative produces its effects of meaning and maintains the enunciate player’s adhesion, assuming that the construction of meaning occurs through interaction. We studied through literature surveys and game practice, the point of view of enunciation strategies used by the enunciator that establish the adhesion contracts with the enunciatee-players in order to understand how the game narrative is built on the "here and now " game route.